Big Data Utilization on Tourism Marketing in Post-Pandemic Recovery Ear: Future Prospect for Indonesia - Ismayanti Istanto; Hapzi Ali; Shine Pintor Siolemba Patiro; Liza Mumtazah Damarwulan (Jurnal Manajemen Indonesia, 2023)
Along with the behaviour changes toward digitalisation in the pandemic, reliable data to manage tourism marketing in Indonesia is needed. The study objectives are to go into detail on the application of big data and identify what kind of data is necessary for tourism marketing based on the previous research. Most studies about big data on tourism marketing come from overseas, with only a few from Indonesian authors. Questions were raised on what big data is used in tourism marketing and what data is needed, mainly for Indonesia. The use of big data and the kind of data for the benefit of tourism marketing in this study has yet to be discovered. The study adopted SLR with the PRISMA approach and continued with bibliometric analysis using VOS Viewers based on keywords and co-occurrence. Scopus is a database source, and 105 articles published from 2002 to 2022 are found. There are six clusters from plotting extensive data application networks. Two forms of big data can be gained to foresee tourism marketing in post-pandemic recovery. The utilisation cluster is the consumer behaviour research, technology operation, social media, future prediction based on network sentiment analysis, and innovation in smart tourism. Data from the tourism industry and non-tourism sector can be utilised. The study implied combining both the tourism and non-tourism sectors as integrated big data in tourism marketing for decision-making in the future. Keywords— big data; marketing; non-tourism; tourism; utilization